The influence of the accelerating voltages on the growth of the square structure during Electron Beam Induced Deposition (EBID) method - Muhammad Afiq Abdul Aziz (Universiti Malaysia Perlis, 2008)
Electron beam induced deposition (EBID) is a method for high-resolution direct material deposition from the gas phase in the Scanning Electron Microscopy (SEM) onto a substrate. In this project, EBID method has been used to deposit the square shape carbon structure on the substrate using the residual gas hydrocarbon as the precursor gas during deposition. With 90000X magnification, the deposition was performed by focusing the high energy electron beam with acceleration voltages of 5 kV~25 kV in a fixed 15 minutes of deposition time directly to the substrate. Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) were used to characterize the growth of the deposited structure in term of thickness, volume and surface roughness influenced by the electron beam acceleration voltages. The growth of the deposited structure was analyzed to increase with higher acceleration voltages. The use of the deposited structure also has been study for further research in EBID applications.